The Viability of Human Security - den Boer, Monica; de Wilde, Jaap (Amsterdam University Press, 2008)
This volume elaborates on the EU report A Human Security Doctrine for Europe, adding an engaging discussion of international legal consequences and operational demands in the European Union's quest for domestic security. Introducing the concept of "Human Security from Below," the editors highlight how people in war-torn countries have no choice but to create their own security arrangements. But such structures, surprisingly, are not unique to war zones, the contributors reveal-human security initiatives from below occur in even the most stable Western countries. Arguing that human security as a concept only makes sense if it covers both foreign and domestic policy concerns, The Viability of Human Security offers concise insights on this largely neglected topic.